Replication Data for: Ceratobasidium sp. is associated with cassava witches’ broom disease, a re-emerging threat to cassava cultivation in Southeast Asia - Leiva Sandoval, Ana Maria; Pardo Garcia, Juan Manuel; Arinaitwe, Warren; Newby, Jonathan Craig; Vongphachanh, Pinkham; Chittarath, Khonesavanh; Oeurn, Samoul; Gil Ordoñez, Alejandra; Rodriguez Villanueva, Rafael Antonio; Cuellar, Wilmer Jose (2025)
These data focus on monitoring cassava crops in Southeast Asia to detect symptoms of Cassava Witches’ Broom Disease (CWBD). Field visits are conducted where plants are randomly selected for photography and assessment for signs of the disease. The collected data include the total number of samples examined, the number of plants testing positive and negative, the incidence rate of the disease in each location, and a confidence interval for incidence estimation